Changes of Locoregional Skin Temperature in Neonates Undergoing Laser Needle Acupuncture at the Acupuncture Point Large Intestine 4 - Kurath-Koller, Stefan (Evid Based Complement Alternat Med, 2015)
Laser acupuncture bears a potential risk for the skin surface, especially in neonates whose skin has histological and physiological peculiarities. We evaluated thermal changes of skin temperature in neonates during laser acupuncture by using a thermal camera (Flir i5, Flir Systems Inc., Portland, USA). Laserneedles (Laserneedle GmbH, Glienicke/Nordbahn, Germany) were fixed to the skin at Large Intestine 4 (LI 4, Hegu), bilaterally. Before application of laser acupuncture (685 nm, 15 mW, 500 μm), as well as after 1, 5, and 10 min, thermographic pictures of both hands were taken. The measuring was carried out on the 23rd day after birth (20 neonates, mean postmenstrual gestational age 38 + 2, mean weight 2604 g). Compared to the initial temperature of 34.2°C on the right hand, the skin temperature had increased to 35.3°C (P < 0.05) after 5 min and up to 36.1°C (P < 0.05) after 10 min of stimulation. Equally, on the left hand, an increase of the skin temperature from 34.5°C to 35.9°C (P < 0.05) and 35.9°C (P < 0.05) was measured. The highest measured skin temperature after 10 min of stimulation amounted to 38.7°C, without any clinically visible changes on the skin surface.